2006
DOI: 10.1167/iovs.05-1208
|View full text |Cite
|
Sign up to set email alerts
|

Lens-Specific Expression of TGF-β Induces Anterior Subcapsular Cataract Formation in the Absence of Smad3

Abstract: Lens-specific expression of TGF-beta1 induced ASC formation in the absence of the Smad3 signaling mediator, suggests that alternative TGF-beta-signaling pathways participate in this ocular fibrotic model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 58 publications
4
73
0
Order By: Relevance
“…That Smad2 phosphorylation is detected in Arf-expressing cells in the embryo suggests but does not prove it to be the crucial Smad in vivo. Its candidacy is strengthened by the fact that Smad3 -/-mice, which are viable, appear to have normal eyes (Banh et al, 2006;Zhu et al, 1998). Formally evaluating the role of Smad2 may require its knockout in cells destined to express the Arf promoter because Smad2 -/-mice suffer early embryonic lethality (Nomura and Li, 1998;Weinstein et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…That Smad2 phosphorylation is detected in Arf-expressing cells in the embryo suggests but does not prove it to be the crucial Smad in vivo. Its candidacy is strengthened by the fact that Smad3 -/-mice, which are viable, appear to have normal eyes (Banh et al, 2006;Zhu et al, 1998). Formally evaluating the role of Smad2 may require its knockout in cells destined to express the Arf promoter because Smad2 -/-mice suffer early embryonic lethality (Nomura and Li, 1998;Weinstein et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…TGFb can terminate the induction of its own target genes by recruiting Smad7, which negatively regulates signalling strength and duration, through formation of a negative-feedback loop [73]. A body of evidence has been obtained regarding the involvement of the classical TGFb/Smad signalling pathway in the pathogenesis of fibrotic disorders of the lens [6,13,14,19]. Work by Saika et al [19] has shown Smad3 and Smad4 to be present in cell nuclei of post-operative human lenses and in injury-induced epithelial to mesenchymal transition (EMT) murine lenses [74], therefore implicating activation by TGFb following trauma.…”
Section: Tgfb: the Orchestrator Of Fibrosismentioning
confidence: 99%
“…The biological function of TGF-β is mediated via the conduction of types I (RI) and II (RII) transmembrane receptors (7). TGF-β is present in almost all cells; therefore, it can influence the physiological function of the majority of tissues correspondingly (8). In vitro, TGF-β Tocotrienol alleviates inflammation and oxidative stress in a rat model of spinal cord injury via suppression of transforming growth factor-β is a potent agent for astrocyte chemotaxis, which can result in the hypertrophy of astrocytes and upregulation of the synthesis of fibronectin and collagen IV (8).…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β is present in almost all cells; therefore, it can influence the physiological function of the majority of tissues correspondingly (8). In vitro, TGF-β Tocotrienol alleviates inflammation and oxidative stress in a rat model of spinal cord injury via suppression of transforming growth factor-β is a potent agent for astrocyte chemotaxis, which can result in the hypertrophy of astrocytes and upregulation of the synthesis of fibronectin and collagen IV (8). Tocotrienols are isomers of vitamin E, located primarily in plants, with antioxidative (9), anti-tumor (10) and neuroprotective functions (11).…”
Section: Introductionmentioning
confidence: 99%